(3JYQja GdYdhes - (3Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj,J (B816 (3g` s
(3ChdgG (B:s
(3hHYO agPg JYQjaGJ LeYJgG hGUWdGMGJ CNPJgG ef cJH Gdbhe hQJHJgG Ydi MQha GdgLGA s
(3BNQgG (B:s
(3bGdhG Gddg JYGdi Ydi GdYQT JMedg GdedGFcI Je GdcJGH HYhf YfGjI Gdedc GdhgGH s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B159 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B728s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B422s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdeYGQa GdYGeIs